INTEGRATED APPROACH IN NUTRIENT MANAGEMENT FOR RICEONION- RESIDUAL GREENGRAM CROP SEQUENCE - MD. RITON CHOWDHURY; SUBORNA ROY CHOUDHURY (The Bioscan, 2014)
To achieve nutritional security keeping food security as a whole without hindering environmental balance, we must have to go for crop diversification in existing cropping pattern. Therefore, with the broader objectives of studying the effect of organic and inorganic sources of nutrients on the productivity, quality improvement of the crops and uptake of nutrients by the crops in sequence, an experiment was conducted in strip plot design with two (2) main plot treatments (B0 i.e. without biofertilizer and B1 i.e. with biofertilizer) and seven (7) sub plot treatments (F1: 100% of the Recommended dose of fertilizers i.e. RDF, F2: 75% of the RDF, F3: 75% of the RDF +25% of N through FYM, F4 : 75% of the RDF +25% of N through vermicompost, F5: 75% of the RDF +25% of N through neem cake, F6: 75% of the RDF +25% of N through groundnut cake and F7 : 75% of the RDF +25% of N through mustard cake replicated thrice. The varieties were Satabdi (IET 4786), Sukhsagar (Local variety) and IPM 2-3 for rice, onion and greengram respectively, replicated thrice during 2011-13 in farmer’s field. It can be concluded that, the combined use of organic, inorganic and biological sources of nutrients showed evidence of excellent results throughout the whole period of supervision (4.31 and 4.54 t ha-1 for rice and 20.73 and 23.81 t ha-1 for onion under main and subplot treatment respectively). In case of residual greengram, the treatment dominance was observed under the main plot treatment having biofertilzer (0.832 t ha-1), sub plot treatment getting organic and inorganic sources of nutrients applied to the previous onion crop (0.861 t ha-1). For maintaining the food security vis-à-vis environmental safety and economic profitability, it may be suggested to adopt the integrated nutrient management practices along with biofertilizer application for rice-onion- residual greengram crop sequence.